(untitled) (RIAF. International Journal of Physical Activity, 2024)
This work arises from the need to provide a response to the theoretical-methodological limitations faced by coaches in directing the historical-sporting training process of young taekwondo athletes, an aspect of significant importance in the comprehensive preparation of taekwondo practitioners during their initial training. A pre-experiment was implemented and evaluated in the training context of young taekwondo athletes, showing through the comparison between the pre-test and post-test that significant changes occur in the historical-sporting training of these athletes, demonstrating the effectiveness of the implemented approach.